Development of an Augmented Reality-Based Flipbook Learning Media on Archive Storage Procedures for 11th-Grade Students at SMK Negeri 44 Jakarta - Sapna Hada Gia Astuti; Dewi Nurmalasari; Bayu Suhendry (The Future of Education Journal, 2026)
This study was motivated by the predominant use of conventional learning media in teaching archive storage procedures at vocational high schools, which made it difficult for students to understand the procedural nature of the subject matter. Observations and a preliminary survey revealed that students understood the material more easily through interactive visualizations and showed a high level of interest in technology-based learning media. These findings indicate the need for innovative learning media that support the implementation of the deep learning approach in the Merdeka Curriculum by providing more concrete, interactive, and contextual learning experiences. This study aimed to develop an Augmented Reality (AR)-based Flipbook learning media for archive storage procedures for Grade XI students at SMK Negeri 44 Jakarta and to analyze its feasibility, practicality, and effectiveness. The study employed the Research and Development (R&D) method using the ADDIE development model, which consists of the analysis, design, development, implementation, and evaluation stages. Data were analyzed using descriptive quantitative analysis through percentage calculations to determine the feasibility and practicality of the developed media, while its effectiveness was evaluated using the N-Gain test based on the pre-test and post-test results. The findings showed that the developed media achieved feasibility scores of 96% from the subject matter expert, 86% from the media expert, and 81% from the instructional design expert, all of which were categorized as highly feasible. Students' responses indicated that the media was highly practical, while its effectiveness was demonstrated by the increase in the average pre-test score from 56.78 to 96.94 on the post-test, with an N-Gain score of 0.93, which is classified as high. Therefore, the Augmented Reality-based Flipbook learning media is considered feasible, practical, and effective for teaching archive storage procedures.